Physical activity patterns following major lower limb amputation - Wójtowicz, Katarzyna; Walczak, Agata; Gajek-Flanczewska, Wiktoria; Wirkijowska, Małgorzata; Woźniak, Paulina; Flanczewski, Sebastian; Wirkijowski, Jakub; Wietrzykowska, Ewa; Śliwińska, Martyna; Podraza, Anna; Sobolewska, Dominika; Michalczyk-Fraszka, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction and aim of study: Lower limb amputation is one of the most common acquired disabilities. The main aim of the study was to assess global trends regarding the procedure, investigate the current trends in post-amputation care, particularly in terms of returning to physical fitness, and identify potential fields of interest in order to improve the everyday life of people with lower limb amputation. Materials and methods: The authors based this review paper on a widespread analysis of scientific articles published in Science Direct, PubMed, UpToDate, Cochrane, Springer, and Google Scholar, the 2021 Global Burden of Disease Study, and government platforms. Results: The collected information emphasizes the existence of numerous barriers discouraging from participating in sports. The post-amputation care is crucial and requires a multidisciplinary team approach. Chronic pain restricts physical activity significantly. Different types of movement focused on specific muscle groups improve functionality. Conclusions: Disability as a result of lower limb amputation is a significant social issue requiring more action to improve its visibility. New strategies ought to be implemented to educate people with disabilities on the importance of physical activity. The new technologies that are currently under investigation may bring some novelty to the topic in the future. Keywords: Amputation, Artificial limbs, Rehabilitation, Para-Sports